Integrating persistent in Elementary School Learning - Gasong, Dina (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses how stackability can be grown as a soft skill for the learner. In general, the primary determinant of the person's success in work is to have the good quiet ability. Cultivating good soft power can only be done through education. One element of soft skills in school is stackability. Stickability is indispensable by leaners to achieve success in learning. Stickability help leaners overcome the obstacles which occur in life. With a stackability, the student can find an away out of faced barries. Stickability is a person's ability to drive herself/himself to be able to meet and overcome obstacles in a problematic situation by focusing on something day want to achieve.The study uses data from the questionnaire and focuses group discussion (FGDs). Observation, Interview, with some teacher and education practice in Toraja 2017. An additional interview with peer lecture of UKI Toraja. FGDs were organizing with some teacher at elementary school. FGDs incourage inter- action among participants that can yield valuable data. Data from the FGDs, observation, questionnaire, and interview underwent the three steps qualitative data analysis: data reduction, data display, and conclusion drawing.Factors the shapes person’s stackability are competitiveness, productive, creative, taking risks, motivation, repairing, perseverance, optimism, embracing change, tenacity. These factors should develop through learning in the classroom. Educators must be able to integrate these elements into their teaching materials. To discuss the factors is done by reading several books related to soft skill and books on learning.The result of this study will show that stackability must be grown in classroom learning through. It can be said activities of the teacher in teacher integrate into each teaching materials that thought, the teacher becomes examples in ethical behaviour, teacher communicates with the student, and teacher need allocate time to convey soft skill values. It can also say the School Effort, while School needs to provide particular time in extra-curricular activities involving the teacher and student as a whole, and School need is to organize events that can foster the values of soft skill. Also, the school need to provide the means to develop an attitude of tolerance and honesty and sportsmanship.